1980
DOI: 10.1271/bbb1961.44.2561
|View full text |Cite
|
Sign up to set email alerts
|

Effects of phosphatidylcholine or ergosteryl oleate on physiological properties of Saccharomyces sake.

Abstract: S. HAYASHIDA and K. OHTA Kyokai No. 7, maintained on slopes of koji extract agar medium, was inoculated into 100ml of basal synthetic medium3) in a 250 ml flask. After 40 hr-incubation at 30•Ž under anaerobic culture conditions,3) about 1 ml of yast culture was again transferred to 100 ml of fresh basal synthetic medium and further incubated for 40 hr at 30•Ž.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

1986
1986
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…Although oleic acid and ergosterol in combination enhanced growth and alcohol endurability, none of these could enhance the fermentative activity of cells (Hayashida and Ohta 1980). As has been discussed earlier supplementation of cells with both PC and (ergos-terol+oleate) promoted the fermentative activity and alcohol endurability of the cells (Hayashida and Ohta 1980) (Table 1).…”
Section: Sterols As Modulators Of Ethanol Tolerancementioning
confidence: 66%
See 1 more Smart Citation
“…Although oleic acid and ergosterol in combination enhanced growth and alcohol endurability, none of these could enhance the fermentative activity of cells (Hayashida and Ohta 1980). As has been discussed earlier supplementation of cells with both PC and (ergos-terol+oleate) promoted the fermentative activity and alcohol endurability of the cells (Hayashida and Ohta 1980) (Table 1).…”
Section: Sterols As Modulators Of Ethanol Tolerancementioning
confidence: 66%
“…Phospholipid supplementation in the growth medium resulted in an increased growth rate, fermentation activity and endurability of sake yeast (Hayashida et al 1975). Subsequent studies by the same group have revealed that the phosphatidylcholine (PC) present in the proteolipid is crucial for ethanol tolerance (Hayashida and Ohta 1980). In addition, an increase of 58.4% in fermentor productivity has been reported for S. cerevisiae by addition of a proteinphospholipid complex (Jin et al 1981).…”
Section: Phospholipids As Modulators Of Ethanol Tolerancementioning
confidence: 99%
“…Nevertheless, S. bayanus yielded the lowest lanosterol:squalene ratio of the yeasts' growth in similar aerobic conditions, suggesting a disparity in the squalene metabolism. Hayashida and Ohta (1980) reported that ergosterol and oleic acid accumulation enhanced yeast stress tolerance by providing rigidity to the membrane. Moreover, a decrease in ergosterol content has been directly related to a decrease in cell viability after stress imposition (Lees et al 1980).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, yeast cells under stress conditions (H 2 O 2 , UV irradiation) lose membrane asymmetry as a result of programmed cell death activation (Del Carratore et al 2002). The loss of PC is important not only because of its role as membrane constituent to maintain membrane integrity, but also because the change in ergosterol/PC ratios acts in detriment of membrane endurability (Hayashida and Ohta 1980). Therefore, the PC level increase in both S. paradoxus and S. bayanus cells grown in supplemented media means not only an improvement in cell viability but also ensures lipid storage to provide for the yeast's needs after recovery from dehydration stress.…”
Section: Effect Of Pc Supplementation Upon Yeast Cell Viabilitymentioning
confidence: 99%
“…In a previous paper [9] studying the effect of ethanol on phospholipids and fatty acids of Schizosaccharomyces pombe, a fission yeast amenable to rigorous biochemical and genetical research [10], we showed that ethanol tolerance may be connected with the high content of oleic acid. Several reports describe the role of sterols on membrane fluidity in the yeast S. cerevisiae [13][14][15]. Several reports describe the role of sterols on membrane fluidity in the yeast S. cerevisiae [13][14][15].…”
Section: Introductionmentioning
confidence: 99%